Analysis of the Implementation of Inactive Records Management Through the Application of Sikardi, a Dynamic Archival Information System, Within the Central Java Provincial Agency for National Unity and Politics in 2025 - Alicia Salsabila Fitriani; Jazimatul Husna (CV. Publikasi Indonesia, 2026)
Inactive records management plays an important role in supporting orderly governmental administration, as these records still possess administrative, legal, and informational value despite their decreasing frequency of use. In an effort to improve the effectiveness of records management, government institutions utilize information technology through the implementation of the Dynamic Archival Information System (SIKARDI). This study aims to analyze the implementation of inactive records management through the application of SIKARDI within the Regional Agency for National Unity and Politics of Central Java Province in 2025. This research employed a qualitative approach with data collection techniques consisting of interviews, observations, and documentation. The informants involved in this study were archivists who directly handled the management of inactive records. The findings indicate that the implementation of SIKARDI has supported inactive records management in a more systematic manner, facilitated the record retrieval process, and improved efficiency in archival management. Nevertheless, the implementation of the system still encounters several challenges, including limited human resources, insufficient technical understanding of the system, and the suboptimal utilization of available features. Therefore, enhancing human resource competencies and strengthening organizational support are necessary to optimize the implementation of SIKARDI in inactive records management.